Economy And Corporations: Measuring How Economic Growth Influences Corporations’ Financial Performance In Indonesia 2013-2020 - Yahya Sudrajat (Eduvest - Journal of Universal Studies, 2021)
Time seris data from the World Bank shows that since Soekarno’s regime to current regime, now in 2020, Indonesia has been having fluctuation of economic growth. Moreover, the pattern of economic growth is on the same rythm with the pattern of Indonesia Stock Exchange’s market capitals. The patterns shows unique correlations, since the investors in Stock Market tend to invest on financially well-performanced companies.  Hence, through this correlation research, the researcher tries to inquire how economic growth influences corporations’ financial performances in Indonesia. Rely on state of the arts, the researcher use ROA and ROE of ten percent samples or 59 companies in Indonesia Stock Exchange as dependent variables in simple linear regression analysis on answering the research questions. Surprisingly, the researcher found unique results from 118 hypotheses, of those all hypotheses, 110 are significant, Seven insignificant, and one is unfulfilled Linearity Test. Astonishingly, of those Seven insignificant results, two companies performed better than economic growth since they able to maintain their finansial performance while whether economy is in crisis or not..